Dual Appell system and Kondrat’ev spaces in analysis on Schwartz spaces - Kachanovskii, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study the biorthogonal Appell system and Kondrat’ev spaces in the case where the parameter of a μ-exponential is perturbed by holomorphic invertible functions. The results obtained are applied to the investigation of pseudodifferential equations.